Catalyst-free gem-chlorosulfurization of difluoromethyl-substituted diazo compounds with disulfide and PhICl2. Issue 37 (6th September 2021) - Li, Jiuling; Li, Bin; Chen, Juan; Jia, Xinyu; Wang, Min; Hao, Chengjun; Zheng, Xinhua; Dai, Hongmei; Hu, Wenhao
Abstract : A series of gem -chlorosulfurization products bearing difluoromethyl substituents were synthesized from TsCF2 CHN2, disulfides and PhICl2 under mild conditions, which could be efficiently converted to multi-component products by a facile operation. Abstract : A series of gem -chlorosulfurization products bearing difluoromethyl substituents were synthesized in high to excellent yields directly from p -toluenesulfonyl difluorodiazoethane (TsCF2 CHN2 ), disulfides and PhICl2 without any catalysts or additives. The mild reaction conditions and high functional group compatibility indicated the utility and sustainability of the method. In addition, the gem -chlorosulfurization products could be efficiently converted to sulfur-containing and aryl substituted difluoromethyl derivatives by a feasible multi-component operation.